Let’s get on-board: a practical framework for designing and implementing educational board games in K-12 classrooms - Vijit V. Nautiyal; Sandro A. Silverio; Erika Eunice P. Salvador; Erika Eunice P. Salvador (Frontiers in Education)
Educational board games are a promising tool for implementing game-based learning to improve the teaching-learning process. However, the absence of comprehensive scholarly guidance on designing educational board games impedes the effective implementation of game-based learning in classrooms. The sparsely available studies on game design frameworks often confine themselves to the design of the educational game itself, without including guidelines for the classroom integration of such games within the design framework. Additionally, the literature often neglects that teachers, burdened by limited time and excessive workload, are often the sole participants in the game design process. To address these gaps, we introduce a practical framework for educators to design and seamlessly integrate educational board games in their classrooms. Our approach prioritizes minimizing additional teacher workload while using game-based learning to foster student-led problem-solving sessions and game revision. Drawing from game design principles and existing literature on game-based learning, we propose a comprehensive framework that guides educators through the design and implementation of educational board games tailored for conducting problem-solving sessions. The framework is validated and refined using qualitative analysis of teacher and student feedback after its seamless integration into the regular mathematics instruction and curriculum of a Philippine K-12 high school. Results indicate positive student experiences and highlight the framework’s efficacy in promoting student engagement, learning outcomes, and teacher convenience. Thematic analysis of student feedback highlights key design preferences and game features that enhance student experiences in GBL sessions. The study contributes to the advancement of GBL methodologies by offering practical guidelines for independent use by educators and promoting exchanges between teacher colleagues. Overall, the proposed framework offers a systematic and feasible approach to designing and implementing educational board games, fostering effective learning experiences in diverse educational contexts.